Fast decap allocation based on algebraic multigrid - Zhuo, Cheng; Hu, Jiang; Zhao, Min; Chen, Kangsheng (International Conference on Computer Aided Design: Proceedings of the 2006 IEEE/ACM international conference on Computer-aided design : San Jose, California; 05-09 Nov. 2006, 2006)
Decap (decoupling capacitor) is an effective technique for suppressing power supply noise. Nevertheless, over-usage of decap usually causes excessive power dissipation. Therefore, the total decap area needs to be minimized subject to power supply noise constraints. This is a complicated nonlinear optimization problem that may have as many as millions of variables. We propose an algebraic multigrid (AMG) based method to handle the high complexity. An error compensation scheme is developed to compensate the accuracy loss during the AMG reduction. A charge based back-mapping method and a few other techniques are suggested to further improve the computation efficiency. Our method is flexible to use and can be easily integrated with other existing decap allocation works. When compared to several previous works, the results from our method are usually the closest to the optimum. Our method also runs fast and can solve circuits with up to 1 million nodes in about 11 minutes. In addition, it has better scalability than the previous works.